The Effects of Adapted Physical Education and Sports Activities on Mental Adjustment Levels and Determination of Communication Skills of Trainable Mentally Handicapped Individuals - Zeynep Yildirim (Journal of Educational Issues, 2024)
This study aimed to determine the effect of exercise training on mental adaptation levels and communication skills in mentally handicapped individuals who were at an educable level. Based on this purpose, the Performance Determination Form for Individuals with Intellectual Disabilities, which was created in 2018 within the scope of the Ministry of National Education, General Directorate of Special Education and Rehabilitation Services, and Hacettepe Spiritual Adaptation Scale developed by Gökler and Öktem (1985) were given to the families of 11 mentally disabled individuals, (3 girls and 8 boys), with a mean age of 11.90. Afterward, 130 hours of adapted physical education and sports activities were applied to 11 trainable mentally retarded individuals, 90 minutes a day, 2 days a week for 12 weeks. After this activity, the same measurements were performed by the families again and the differences were examined. As a result of SPSS, although there was no statistical significance in the behavioural and neurotic results, which were the sub-dimensions of the psychological adjustment variable, a decrease was observed in the post-test mean scores after the exercise program was applied. This result proves that physical education and sports activities have positive effects on the mental adjustment of individuals with educable mental disabilities. Findings on receptive language skills and expressive language skills, which were sub-dimensions of the participants’ communication skills, were examined. While the mean receptive language skills pre-test score was 31.72±3.00, the post-test mean score was 127.09±6.18, the expressive language skills pre-test mean score was 13.27±2.37, and the post-test mean score was 54.63±1.56. The observed difference was statistically significant. As can be seen, it was determined that physical education and sports activities applied have positive effects on individuals with educable mental disabilities, both in terms of psychological adaptation and communication skills. As a result, it has been determined in this research that physical education activities, which are an integral part of education, are very beneficial in terms of mental adaptation and communication skills, which are vital for individuals with mental disabilities.